P127 Inflammatory Bowel Disease-associated colorectal cancers: retrospective cohort study from a tertiary centre surveillance programme over 10 years. (30th January 2023) - Porter, R; Gillespie, S L; Song, M; Ball, G; Crawford, A; Churchhouse, A; Gardner, M; Plevris, N; Chuah, C S; Brindle, W; Watson, E; Jenkinson, P; et al.
Abstract: Background: Patients with IBD have increased risk for developing colorectal cancer (CRC), with poorer survival, compared to those without IBD. Despite surveillance colonoscopy, IBD post-colonoscopy CRC (PCCRC) rates are unacceptably high at 28-45%. We define surveillance colonoscopy quality, IBD-dysplasia and IBD-CRC prevalence, IBD-CRC characteristics, and IBD PCCRC rates at a tertiary IBD centre. Methods: The GI Reporting Tool (Unisoft Medical Systems) was searched for IBD surveillance colonoscopy reports from April 2008–December 2018. Electronic medical records were reviewed. IBD phenotype and diagnosis date was confirmed on the Lothian IBD Registry. Follow-up was until September 2022. Results: 1892 colonoscopies from 1262 patients were included. Median follow-up was 7.1 (4.4, 9.5) years. 885/1262 (70.1%) had UC, 344/1262 (27.3%) had Crohn's, and 33/1262 (2.6%) had IBD-U. Median disease duration at colonoscopy was 16.8 (11, 24.6) years. 1825/1892 (96.5%) colonoscopies achieved caecal intubation, 1735/1840 (94.3%) adhered to biopsy guidelines and 704/1892 (37%) used chromoendoscopy. Histological inflammation was identified in 873/1823 (47.9%) cases; 57.2% in the right colon. Bowel preparation was poor in 194/1892 (10.3%) procedures and the most documented reason for not performing chromoendoscopy. Poor bowel preparation was associated with 23/60 (38.3%) poorly tolerated and 29/52 (55.8%) incomplete colonoscopies. Moviprep was superior to Picolax (p<0.001). GI physicians were more likely to use chromoendoscopy (p<0.001), biopsy per guideline (p<0.001), and identify dysplasia (p=0.012) compared to surgical colleagues. Dysplasia was identified in 145/1892 (7.7%) colonoscopies: 84/1892 (4.4%) sporadic, 22/1892 (1.2%) IBD-associated, and 39/1892 (2.1%) unspecified. IBD-CRC is rare, at 0.8 cases per 1000 patient years. Within the study period, 20/1262 (1.6%) patients had CRC diagnosed. 17/20 (85%) had UC and 3/20 (15%) had Crohn's. 15/17 (88%) UC patients had E3 disease. 11/20 (55%) presented with lymph node or distant metastasis. 8/20 (40%) tumours had mucinous differentiation; only 1/15 (6.7%) was well differentiated. IBD-CRC patients had longer disease duration (28.3 (19.7, 37.8) years) compared to patients without CRC (22.25 (16.42, 29.85) years) at follow-up (p=0.028). The 3-year PCCRC rate was 15%. Conclusion: IBD-CRC is rare however IBD PCCRC rates are unacceptably high. While this may reflect disease biology, a new approach to IBD surveillance is urgently needed. Interventions could include dedicated IBD surveillance lists, patient education around bowel preparation, and pre-screening for inflammation (e.g. faecal calprotectin). Cancer registry database linkage is now essential for us to identify IBD-CRC cases not identified by surveillance.